1998
DOI: 10.1006/jmaa.1998.5948
|View full text |Cite
|
Sign up to set email alerts
|

An Addendum to Krein's Formula

Abstract: We provide additional results in connection with Krein's formula, which describes the resolvent difference of two self-adjoint extensions A 1 and A 2 of a densely defined closed symmetric linear operatorȦ with deficiency indices n n n ∈ ∪ ∞ . In particular, we explicitly derive the linear fractional transformation relating the operator-valued Weyl-Titchmarsh M-functions M 1 z and M 2 z corresponding to A 1 and A 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
105
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 13 publications
(23 reference statements)
0
105
0
Order By: Relevance
“…Our principal motivation in studying this problem stems from our general interest in operator-valued Herglotz functions (cf. [12], [37], [38], [39], [40], [41], [44], [85]) and its possible applications in the areas of inverse spectral theory and completely integrable systems. More precisely, using higher-order expansions of the type (1.1), one can prove trace formulas for Q(x) and certain higher-order differential polynomials in Q(x), following an approach pioneered in [42] (see also [35], [36]).…”
Section: Introductionmentioning
confidence: 99%
“…Our principal motivation in studying this problem stems from our general interest in operator-valued Herglotz functions (cf. [12], [37], [38], [39], [40], [41], [44], [85]) and its possible applications in the areas of inverse spectral theory and completely integrable systems. More precisely, using higher-order expansions of the type (1.1), one can prove trace formulas for Q(x) and certain higher-order differential polynomials in Q(x), following an approach pioneered in [42] (see also [35], [36]).…”
Section: Introductionmentioning
confidence: 99%
“…For such problems, we note in the subsequent lemma that for fixed β, varying the boundary data α produces Weyl-Titchmarsh matrices M (z, c, x 0 , α, β) related to each other via linear fractional transformations (see also [47], [52] for a general approach to such linear fractional transformations).…”
Section: Weyl-titchmarsh Matrices For Hamiltonian Systemsmentioning
confidence: 99%
“…In a recent paper by Gesztesy et al [11], the authors have revisited Krein's formula associated with self-adjoint extensions of a densely defined symmetric operator. They showed that the coefficients in Krein's formula can be expressed in terms of the classical von Neumann parameterization formulas.…”
Section: Introductionmentioning
confidence: 98%